Multinationals on trial foreign investment matters - Petras, James F.; Veltmeyer, Henry (Ashgate Pub., 2007)
The role and economic power of corporations that dominate the world economy has generated considerable controversy. The most heated debate and the most critical questions, surrounding the role of multinational corporations has to do with foreign direct investment (FDI). FDI is a mechanism for empire-centred capital accumulation, a powerful lever for political control and for reordering the world economy.